Perancangan Video Motion Graphic Sebagai Media Marketing Studi Kasus di PT. Bakool Nusantara - Rudjiono, Rudjiono; Setiyo Adi Nugroho; Agus Priyadi; Akhmad Cholif Agung Yuliyanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
PT. Bakool Nusantara is a startup that provides fresh vegetable products with an online BTB and BTC business concept. This research aims to enhance brand recognition and introduce the Bakool Apps application to PT. Bakool Nusantara customers through the design of motion graphic videos as a marketing medium. The company has encountered challenges in effectively introducing the Bakool Apps brand and application to customers, thus requiring innovation in marketing strategy. This study employs a case study method at PT. Bakool Nusantara to gain a comprehensive understanding of the company's challenges. Subsequently, the research focuses on the design of motion graphic videos as a solution to enhance brand recognition and introduce the Bakool Apps application. The use of motion graphic techniques is expected to provide an engaging and effective visual experience in conveying information to customers. The validation results from expert assessments of the motion graphic video product obtained a score of 4.7 out of 5, indicating high validity. Similarly, expert assessments of content validity yielded a score of 4.7 out of 5, suggesting high validity as a marketing media tool. User validation results also scored 4.652 out of 5, indicating high effectiveness for use. Thus, based on expert and user validation results, the produced video product is deemed valid and suitable for production as a product. Keywords: Motion Graphic, Video, Media Marketing